Composting Layers of Christchurch History - Rebecca Ream (Genealogy, 2021)
This is a poetic compost story. It is a situated tale of how I gradually began to shred my fantasy of being a self-contained responsible individual so I could become a more fruitful response-able Pākehā (for the purposes of this paper, a descendant of colonial settlers or colonial settler) from Christchurch (the largest city in the South Island of New Zealand), Aotearoa (The Māori (the Indigenous people of New Zealand) name for New Zealand) New Zealand. Poetic compost storying is a way for me to turn over Donna Haraway’s composting ethico-onto-epistemology with critical family history and critical autoethnography methodologies. To this end, I, in this piece, trace how I foolishly believed that I could separate myself from my colonial family and history only to find that I was reinscribing Western fantasies of transcendence. I learnt by composting, rather than trying to escape my past, that I could become a more response-able Pākehā and family member.